BABY HANDLING AND INFANTS FEEDING - Lara Drole; Mojca Žagar Okorn (Slovenska pediatrija)

(untitled)
With the correct approach to baby handling, we aim to sup-port optimal development and provide diverse sensory-motor experiences. Additionally, we encourage the baby‘s independence and help prevent improper motor patterns, which is essential to integrate into everyday activities. When discussing the feeding of newborns and infants, it is important to consider not only the appropriate volume the child can consume but also the quality of sucking, which can vary according to several factors. Through sucking, babies develop numerous other skills that are significant for their overall quality of life.